Opini Audit Sebelumnya, Financial Distress, Auditor Switching dan Opini Audit Going Concern - Senjaya, Kevin; Budiartha, I Ketut (E-Jurnal Akuntansi, 2022)
This study aims to prove whether the previous audit opinion, financial distress, and auditor Switching on going concern audit opinion. This research was conducted in a manufacturing company listed on the Indonesia Stock Exchange in 2013-2017. Samples were obtained by purposive sampling method. The number of samples obtained is 43 companies. The data analysis technique used is the Wald test. Based on the results of the study, it is known that the previous audit opinion has no effect on the going concern audit opinion. Financial distress has a negative effect on going concern audit opinion. Auditor Switching has a positive effect on going concern audit opinion. The theoretical implication of this research is as an additional reference for further research related to going concern audit opinion and agency theory. Keywords : Going Concern Audit; Previous Audit Opinion; Financial distress; Auditor Switching.